How regional economic integration influence on urban land use efficiency？ A case study of Wuhan metropolitan area, China. (January 2020) - Gao, Xin; Zhang, Anlu; Sun, Zhanli
Highlights: TFULE in Wuhan metropolitan area is spatially autocorrelated and exhibit clustering patterns. Regional economic linkage will increase TFULE of counties and their neighbors, especially in the core development zones. Industrial structural upgrading can improve TFULE, but it brings down neighbors' TFULE except for the core development zones. Abstract: Many emerging economies have experienced rapid urbanization in an unprecedented scale and speed in the past few decades. While the urban expansion has led to the formation of metropolitan areas and promoted the economic development, it also exerts enormous pressure on environment and threatens food security. The efficient use of urban land becomes one of paramount challenges for governments to achieve sustainable and balanced growth. However, most literature has ignored the fact that in the metropolitan areas, the regional economic integration may cause the urban input-output structure readjustment through the flow of the market factors and industrial structure redistribution, thus ultimately influencing the urban land use efficiency. In this paper, we use the Wuhan metropolitan area, a rapidly growing urban agglomeration, in central China as a case to investigate the spatial spillover effects of regional economic integration on urban land use efficiency in the core development zones and the restricted development zones from 2001 to 2015. We quantify the total factor urban land use efficiency (TFULE) with data envelopment analysis, and then estimate the underlying determinants of the TFULE with a spatial panel model. Results show that 1) the TFULE values across counties (districts) are spatially autocorrelated and exhibit clustering patterns during the study period; 2) total external economic linkage (TEEL), quantified with a gravity model, has a significantly positive effect on TFULE of counties (districts) and neighboring counties (districts), especially in the core development zones; 3) the industrial structure upgrading improves the TFULE of counties (districts), but it brings down the TFULE in surrounding areas except for the core development zones. We conclude that regional economic integration in the metropolitan areas can facilitate the optimal allocation of resources for improving urban land use efficiency during the socioeconomic transformation process. Therefore, we suggest the government should establish a distinctly cross-regional fiscal compensation system to improve the regional coordination and balance in economic development.